Protein Synthesis Inhibition and Activation of the c-Jun N-Terminal Kinase Are Potential Contributors to Cisplatin Ototoxicity - Nicholas, Brian D.; Francis, Shimon; Wagner, Elizabeth L.; Zhang, Sibo; Shin, Jung-Bum (Frontiers in Cellular Neuroscience, 2017)
Cisplatin has been regarded as an effective and versatile chemotherapeutic agent for nearly forty years. Though the associated dose-dependent ototoxicity is known, the cellular mechanisms by which cochleovestibular hair cell death occur are not well understood. We have previously shown that aminoglycoside ototoxicity is mediated in part by cytosolic protein synthesis inhibition. Despite a lack of molecular similarity, aminoglycosides were shown to elicit similar stress pathways to cisplatin. We therefore reasoned that there may be some role of protein synthesis inhibition in cisplatin ototoxicity. Employing a modification of the bioorthogonal noncanonical amino acid tagging (BONCAT) method we evaluated the effects of cisplatin on cellular protein synthesis. We show that cisplatin inhibits cellular protein synthesis in organ of Corti explant cultures. Similar to what was found after gentamicin exposure, cisplatin activates both the c-Jun N-terminal kinase (JNK) and mammalian target of rapamycin (mTOR) pathways. In contrast to aminoglycosides, cisplatin also inhibits protein synthesis in all cochlear cell types. We further demonstrate that the multikinase inhibitor sorafenib completely prevents JNK activation, while providing only moderate hair cell protection. Simultaneous stimulation of cellular protein synthesis by insulin, however, significantly improved hair cell survival in culture. The presented data provides evidence for a potential role of protein synthesis inhibition in cisplatin-mediated ototoxicity.